2009
DOI: 10.1186/1471-2318-9-s1-a57
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of breast cancer in elderly patients

Abstract: The number of elderly patients with breast cancer is increasing. The purpose of this study was to evaluate the outcome of treatment of elderly women with breast cancer. We have explored the clinical and biologic characteristics of a group of patients aged 65 years and over affected with breast cancer. We have also identified specific subsets of elderly patients with breast cancer who have survival similar to that expected in the general population irrespective of disease status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…While there have been Italian hospital-based studies of cancer outcomes 13,15 , our approach facilitates the study of these quality-of-care indicators for large populations when registry data are unavailable. This approach allows health care managers and medical directors to assess and compare quality of care at a regional level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been Italian hospital-based studies of cancer outcomes 13,15 , our approach facilitates the study of these quality-of-care indicators for large populations when registry data are unavailable. This approach allows health care managers and medical directors to assess and compare quality of care at a regional level.…”
Section: Discussionmentioning
confidence: 99%
“…Italian radiotherapy practices and compared these to national and international guidelines 13,14 . Other research on follow-up care has been based in selected oncology units or hospitals, such as a recent single hospital study of chemotherapy and radiation therapies for elderly women 15 .…”
Section: Surveys Of Italian Radiation Oncology Centers Studiedmentioning
confidence: 99%
“…As a consequence, elderly patients cannot be treated in an aggressive way though they are diagnosed at later stages than younger patients [9,19,20]. When assessed from the viewpoint of surgical treatment, it has been reported that a more limited surgical treatment is administered in the elderly and that this situation is much more apparent in patients aged ≥80 years [6].…”
Section: Discussionmentioning
confidence: 99%
“…The situation is similar with radiotherapy and chemotherapy. While in various studies patients aged ≥70 and ≥80 years are emphasized, the consensus is that the patients in this age group receive less chemotherapy and radiotherapy but more hormonal therapy [6,7,19,20]. …”
Section: Discussionmentioning
confidence: 99%